A study on the safety culture profile of manufacturing industries - Muhammad Rafiq Farhan, Nor Bahtier (2025)
Occupational safety is a crucial factor in the manufacturing industry due to its immense exposure to hazard and risk from equipment, machinery, and working procedures. This study aims to examine the safety culture profile of manufacturing industries according to key dimensions of management commitment, safety policy sufficiency, employee involvement, safety communication, reporting, and handling accidents. Information were collected using Nordic Occupational Safety Climate Questionnaire (NOSACQ-50) and computed using statistical software to quantify safety climate levels and levels of correlation with organizational performance. The study was conducted at a factory in Padang Lalang, Kuantan, Pahang with local and foreign workers. Results indicated that worker participation and management commitment were significant factors in the overall safety culture. The findings also indicated that although there existed policies of safety, open communication and active participation of workers were essential in order to improve safety performance and reduce the incidence of occupational injury. By defining the safety culture, this research emphasizes the need for a safe and participative safety climate for preventing workplace accidents and promoting employees' well-being. The results may help companies enhance their safety programs and support regulatory adjustments to occupational health standards. Generally, the project provides groundwork for future interventions and may reveal paths for moving towards safer industrial practice across the sector